PENGGUNAAN MEDIA GOOGLE FORM PADA MASA PANDEMI COVID-19 DALAM PENILAIAN HASIL BELAJAR PESERTA DIDIK KELAS VI DI SEKOLAH DASAR NO. 1 SIBANGGEDE KABUPATEN BADUNG (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Google form is an application that can be used for free to assist teachers in assessing student learning outcomes during the covid-19 pandemic. This study aims to 1) To find out the process of using google form media during the covid-19 pandemic, 2) To find out the responses of teachers and students to the use of google form media during the covid-19 pandemic, 3) To find out the obstacles faced in the use of google form media. media google form during the covid-19 pandemic. The theory used to analyze the problem formulation is the behavioristic theory of Burrhus Frederic Skinner and Edward Lee Thorndike. Data collection methods used are interviews, observation, documentation studies and literature study. The data that has been collected was analyzed by using descriptive qualitative analysis method through data reduction, data presentation and conclusion drawing. The results showed that, the process of using google form media during the covid-19 pandemic in assessing the learning outcomes of class VI students at Elementary School No. 1 Sibanggede includes 3 stages, namely the preparation stage, the implementation stage, and the final stage. The teacher's response regarding the use of the google form media, which is easy to use and quite effective, does not require a lot of money, only requires a stable internet network and student responses regarding the use of google form media, namely the google form is easy to use and looks attractive, just by clicking on the shared link via WhatsApp Groups. Constraints faced in using google form media are unstable internet network, limited internet quota, not all students have cellphones that support learning, technical problems with the devices used.